Fibre boards and composites from wet preserved hemp. (13th August 2009) - Pecenka, Ralf; Furll, Christian; Idler, Christine; Grundmann, Philipp; , Ljubomir Radosavljevic
It is absolutely necessary to reduce plant investments and processing costs in order to make natural fibres more attractive for farmers and industry. Conventional hemp fibre production is based on field drying and straw retting – connected with a high weather risk. Therefore, a novel weather-independent technique has been developed. Hemp is harvested by means of a chopper followed by anaerobic storage. A pilot plant with a processing capacity of 300 kg h −1 (dm) fibre material has been built up and tested. The whole plant material can be processed to products like insulation materials, fibre boards or granulate for injection moulding.